Novel electrolytes for lithium ion batteries
By using cosolvent electrolytes containing ring-shaped and linear carbonate in the lithium-ion battery pack, the problem of poor cycling performance of the lithium-ion battery pack during the thermal lamination manufacturing process is solved, and higher thermal stability and low-temperature performance are achieved.
Patent Information
- Application Number
- CN202311203864.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
During the thermal lamination manufacturing process, existing lithium-ion battery packs have poor circulation performance due to solvent expansion and dimethyl carbonate evaporation.
An electrolyte containing a lithium salt and a co-solvent is used, wherein the co-solvent consists of a solvent containing a cyclic carbonate and a solvent containing a linear carbonate to improve the thermal stability and low temperature properties of the electrolyte.
By using co-solvent electrolytes containing ring-shaped and linear carbonates, the expansion of the lithium-ion battery pack at high temperatures is suppressed, the fast charging capacity and DC fast charging cycle life are improved, and the low-temperature discharge capacity is maintained.
Smart Images

Figure CN119650862A_ABST
Abstract
Description
Technical Field
[0001] The subject disclosure relates to novel electrolytes for lithium-ion batteries and methods of making such batteries. Background Art
[0002] The subject disclosure relates to novel electrolytes for lithium-ion batteries and methods of making such batteries.
[0003] High energy density electrochemical cells, such as lithium-ion batteries, are used in a variety of consumer products and vehicles, such as battery packs or hybrid electric vehicles. As battery power and lifespan continue to improve, battery-powered vehicles appear promising as a transportation option.
[0004] Lithium silicon oxide (LSO) has been shown to provide lithium-ion batteries with high energy density and fast charging capability when used in the anode active layer. Lithium-ion batteries (using lithium silicon oxide (LSO)) in the anode active layer typically contain an electrolyte containing a linear carbonate solvent, such as ethylene carbonate and dimethyl carbonate. Lithium-ion batteries containing lithium silicon oxide as the anode active material and an electrolyte containing a linear carbonate solvent are typically manufactured in the form of pouch cells.
[0005] Pouch cells are generally manufactured by a hot lamination process performed at a temperature of 65 to 85° C. However, the hot lamination process causes solvent expansion and evaporation of dimethyl carbonate, resulting in poor cycling performance of lithium-ion batteries. Therefore, it is desirable to use an electrolyte that can better withstand the lithium battery manufacturing process. Summary of the invention
[0006] In one embodiment, the electrolyte comprises a lithium salt and a co-solvent, wherein the co-solvent comprises a cyclic carbonate-containing solvent and a linear carbonate-containing solvent.
[0007] In another embodiment, the lithium salt includes a primary lithium salt and a secondary lithium salt.
[0008] In yet another embodiment, the primary lithium salt is LiPF6.
[0009] In yet another embodiment, the secondary lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalato)borate (LiBOB), lithium (difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide (LiDFTFSI), lithium difluorooxalatoborate (LIODFB), or a combination thereof.
[0010] In yet another embodiment, the lithium salt is LiPF6.
[0011] In yet another embodiment, the cyclic carbonate-containing solvent comprises a 5-membered ring with a carbonate moiety having a boiling point greater than 200°C and a melting point less than 50°C.
[0012] In yet another embodiment, the cyclic carbonate-containing solvent has a boiling point greater than 225°C and a melting point less than -25°C.
[0013] In yet another embodiment, the cyclic carbonate-containing solvent has the structure of formula (1):
[0014]
[0015] wherein R1 and R2 may be the same or different and are independently hydrogen, C1 to C5 alkyl or halogen.
[0016] In yet another embodiment, R1 is hydrogen and R2 is hydrogen, C1-C3 alkyl or fluorine.
[0017] In yet another embodiment, the cyclic carbonate-containing solvent is ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, fluoroethylene carbonate (FEC), or a combination thereof.
[0018] In yet another embodiment, the cyclic carbonate-containing solvent is propylene carbonate (PC), fluoroethylene carbonate (FEC), or a combination thereof.
[0019] In yet another embodiment, the cyclic carbonate-containing solvent is present in an amount of 5 wt % to 87 wt %, based on the total weight of the electrolyte.
[0020] In yet another embodiment, the linear carbonate-containing solvent is ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl butyrate, methyl butyrate, or a combination thereof.
[0021] In yet another embodiment, the linear carbonate-containing solvent is ethyl methyl carbonate, dimethyl carbonate, or a combination thereof.
[0022] In one embodiment, the battery pack includes an anode, a cathode, an electrolyte and a separator. The anode includes an anode current collector and an anode active layer. The anode active layer comprises a lithiated silicon oxide or a combination of lithiated silicon oxide and carbon. The lithiated silicon oxide or a combination of lithiated silicon oxide and carbon is present in an amount of 20 wt % or more based on the total weight of the anode active layer. The cathode includes a cathode current collector and a cathode active layer. The separator is disposed between the anode and the cathode. The electrolyte comprises a lithium salt and a cosolvent, wherein the cosolvent comprises a solvent containing a cyclic carbonate and a solvent containing a linear carbonate.
[0023] In yet another embodiment, the lithiated silicon oxide has the formula Li y SiOx And wherein the combination of lithiated silicon oxide and carbon has the formula Li y SiO x -C; wherein y is 0 to 1, and x is 0 to 2.
[0024] In yet another embodiment, the cyclic carbonate-containing solvent comprises a 5-membered ring with a carbonate moiety having a boiling point greater than 200°C and a melting point less than 50°C.
[0025] In yet another embodiment, the cyclic carbonate-containing solvent has a boiling point greater than 225°C and a melting point less than -25°C.
[0026] In yet another embodiment, the linear carbonate-containing solvent is ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl butyrate (EB), methyl butyrate (MB), or a combination thereof.
[0027] In one embodiment, a method for manufacturing a lithium ion battery includes stacking an anode, a cathode, and a separator together. The separator is disposed between the anode and the cathode. The anode and the cathode are in contact with the anode terminal and the cathode terminal, respectively. The anode and the cathode are placed in a bag. The bag in which the anode, the cathode, and the separator are disposed is formed into a laminate at a temperature of 60 to 85° C. The electrolyte is disposed in the bag to form a lithium ion battery. The anode includes an anode active layer, which includes a combination of 20% by weight or more of a lithiated silicon oxide or a lithiated silicon oxide and carbon based on the total weight of the anode active layer. The electrolyte includes a lithium salt and a cosolvent. The cosolvent includes a solvent containing a cyclic carbonate and a solvent containing a linear carbonate.
[0028] The present invention discloses the following scheme:
[0029] Scheme 1. An electrolyte comprising:
[0030] lithium salts; and
[0031] A co-solvent; wherein the co-solvent comprises a solvent containing a cyclic carbonate and a solvent containing a linear carbonate.
[0032] Option 2. The electrolyte according to Option 1, wherein the lithium salt comprises a primary lithium salt and a secondary lithium salt.
[0033] Option 3. An electrolyte according to Option 2, wherein the primary lithium salt is LiPF6.
[0034] Option 4. An electrolyte according to Option 2, wherein the secondary lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalato)borate (LiBOB), lithium (difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide (LiDFTFSI), lithium difluorooxalatoborate (LIODFB), or a combination thereof.
[0035] Option 5. The electrolyte according to Option 1, wherein the lithium salt is LiPF6.
[0036] Embodiment 6. The electrolyte according to Embodiment 1, wherein the cyclic carbonate-containing solvent comprises a 5-membered ring having a carbonate moiety, which has a boiling point greater than 200° C. and a melting point less than 50° C.
[0037] Embodiment 7. The electrolyte according to Embodiment 6, wherein the solvent containing the cyclic carbonate has a boiling point greater than 225°C and a melting point less than -25°C.
[0038] Scheme 8. The electrolyte according to Scheme 1, wherein the cyclic carbonate-containing solvent has a structure of formula (1):
[0039]
[0040] wherein R1 and R2 may be the same or different and are independently hydrogen, C1 to C5 alkyl or halogen.
[0041] Scheme 9. An electrolyte according to Scheme 8, wherein R1 is hydrogen, and R2 is hydrogen, a C1-C3 alkyl group or fluorine.
[0042] Embodiment 10. The electrolyte according to Embodiment 1, wherein the cyclic carbonate-containing solvent is ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, fluoroethylene carbonate (FEC), or a combination thereof.
[0043] Embodiment 11. The electrolyte according to Embodiment 1, wherein the cyclic carbonate-containing solvent is propylene carbonate (PC), fluoroethylene carbonate (FEC), or a combination thereof.
[0044] Embodiment 12. The electrolyte according to Embodiment 1, wherein the cyclic carbonate-containing solvent is present in an amount of 5 wt % to 87 wt %, based on the total weight of the electrolyte.
[0045] Embodiment 13. The electrolyte according to Embodiment 1, wherein the linear carbonate-containing solvent is ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl butyrate, methyl butyrate, or a combination thereof.
[0046] Embodiment 14. The electrolyte according to Embodiment 13, wherein the linear carbonate-containing solvent is ethyl methyl carbonate, dimethyl carbonate, or a combination thereof.
[0047] Solution 15. A battery pack comprising:
[0048] an anode; wherein the anode comprises an anode current collector and an anode active layer; wherein the anode active layer comprises lithiated silicon oxide or a combination of lithiated silicon oxide and carbon; wherein the lithiated silicon oxide or the combination of lithiated silicon oxide and carbon is present in an amount of 20 wt % or greater based on the total weight of the anode active layer;
[0049] Cathode; wherein the cathode comprises a cathode current collector and a cathode active layer;
[0050] A separator disposed between the anode and the cathode; and
[0051] An electrolyte; wherein the electrolyte comprises a lithium salt and a co-solvent; wherein the co-solvent comprises a solvent containing a cyclic carbonate and a solvent containing a linear carbonate.
[0052] Option 16. A battery pack according to Option 15, wherein the lithiated silicon oxide has a formula Li y SiO x And wherein the combination of lithiated silicon oxide and carbon has the formula Li y SiO x -C; wherein y is 0 to 1, and x is 0 to 2.
[0053] Embodiment 17. The battery pack according to Embodiment 15, wherein the cyclic carbonate-containing solvent comprises a 5-membered ring having a carbonate moiety, which has a boiling point greater than 200° C. and a melting point less than 50° C.
[0054] Embodiment 18. The battery pack according to Embodiment 15, wherein the solvent containing the cyclic carbonate has a boiling point greater than 225°C and a melting point less than -25°C.
[0055] Embodiment 19. The battery pack according to Embodiment 15, wherein the linear carbonate-containing solvent is ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl butyrate (EB), methyl butyrate (MB), or a combination thereof.
[0056] Solution 20. A method for manufacturing a lithium-ion battery pack, comprising:
[0057] stacking an anode, a cathode, and a separator together; wherein the separator is disposed between the anode and the cathode; wherein the anode comprises an anode active layer, the anode active layer comprising 20 wt % or more of lithiated silicon oxide or a combination of lithiated silicon oxide and carbon based on the total weight of the anode active layer;
[0058] contacting the anode and the cathode with an anode terminal and a cathode terminal, respectively;
[0059] placing the anode and the cathode into a bag;
[0060] laminating the bag in which the anode, the cathode, and the separator are disposed at a temperature of 60° C. to 85° C. to form a laminate; and
[0061] An electrolyte is disposed in the bag to form a lithium ion battery; wherein the electrolyte comprises a lithium salt and a co-solvent; wherein the co-solvent comprises a cyclic carbonate-containing solvent and a linear carbonate-containing solvent.
[0062] The above features and advantages and other features and advantages of the present disclosure will become more apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Other features, advantages and details appear, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:
[0064] Figure 1 is a cross-sectional view of a lithium-ion pouch cell.
[0065] Figure 2 It is a graph that plots voltage (V) versus capacity ((Ah) - ampere-hour) at 25°C and a capacity rate of 1 coulomb (C).
[0066] Figure 3 is a graph showing the state of charge (SOC) in percent versus the charging time (in minutes) required to reach a specific charge capacity;
[0067] Figure 4A is a graph depicting discharge capacity retention (in percent) versus cycle number; and
[0068] Figure 4B A graph that plots voltage (V) versus capacity (ampere-hours). DETAILED DESCRIPTION
[0069] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses.
[0070] According to an exemplary embodiment, disclosed herein is an electrolyte for a lithium-ion battery pack, comprising a solvent containing a cyclic carbonate in addition to a solvent containing a linear carbonate. This combination of compatible cyclic and linear carbonate-containing solvents (hereinafter referred to as a "co-solvent") has a boiling point above 100°C and a melting point below -10°C (minus 10°C), which provides the electrolyte with thermal stability at elevated temperatures used in a pouch cell lamination method. The low melting point enhances the low temperature performance of the battery. Compared to an electrolyte containing one or more linear carbonate-containing solvents, the disclosed co-solvent-containing electrolyte suppresses the expansion of a pouch cell containing an anode having more than 40% lithium silicon oxide during a thermal lamination pouch cell manufacturing method (which is performed at a temperature of 80°C). Pouch cells containing electrolytes containing co-solvents exhibit excellent fast charging capabilities (these cells can be charged to up to 85% of the total state of charge (SOC) in 20 minutes), enhanced DC fast charge (DCFC) cycle life, and low room temperature discharge capacity (greater than or equal to about 55% of the -20°C / 25°C 1C capacity retention rate). The term "1C capacity" refers to 1 coulomb (C) discharge capacity at -20°C (minus 20°C). Using a constant current constant voltage (CCCV) charging protocol, the battery was charged to 4.2V at C / 3 with a C / 20 taper at 25°C, and then the battery was kept at -20°C (minus 20°C) for 6 hours and discharged to a voltage of 2.5V at 1C.
[0071] Also disclosed herein is a lithium ion battery pack comprising the aforementioned electrolyte. The electrolyte can be used for a pouch cell lithium ion battery pack containing lithiated silicon oxide in the anode active layer. The anode active layer preferably contains lithiated silicon oxide in an amount greater than 20 wt % based on the total weight of the anode active layer. The term "lithiated" means that a material (e.g., silicon oxide) is combined with lithium or a lithium compound or impregnated with lithium or a lithium compound. The use of the aforementioned electrolyte (with a co-solvent) allows high temperature lamination of the battery pack because the higher boiling point of the solvent containing the cyclic carbonate prevents evaporation of the solvent and expansion of the battery pack.
[0072] Figure 1 A lithium ion pouch cell 100 is described in detail. An anode 120 for the pouch cell 100 includes an anode current collector 102 and an anode active layer 104. A cathode 130 for the pouch cell includes a cathode current collector 112 and a cathode active layer 110. A separator 108 separates the anode 120 from the cathode 130. An electrolyte 106 is disposed between the anode active layer 104 and the separator 108 in the pouch cell 100, and is also disposed between the cathode active layer 110 and the separator 108 in the pouch cell 100. The anode 120, the cathode 130, the separator 108, and the electrolyte 106 are packaged in a pouch 103.
[0073] Anode current collector 102 and cathode current collector 112 include metal. Examples of suitable metals for anode current collector 102 include stainless steel, copper, nickel, iron, titanium, or a combination thereof. Examples of suitable metals for cathode current collector 112 include stainless steel, aluminum, nickel, iron, titanium, or a combination thereof.
[0074] The electrolyte comprises a cosolvent (a solvent containing a cyclic carbonate and a solvent containing a linear carbonate), a lithium salt and an additive. The solvent containing the cyclic carbonate is preferably a 5-membered ring with a carbonate moiety. Preferably, it has a boiling point greater than 200°C, preferably greater than 225°C, and a melting point less than 50°C, preferably less than 0°C, and more preferably less than -25°C (minus 25°C). In one embodiment, the solvent containing the cyclic carbonate has a structure of the following formula (1).
[0075]
[0076] Wherein R1 and R2 can be identical or different, and independently be hydrogen, C1 to C5 alkyl or halogen.In one embodiment, R1 is hydrogen, and R2 is hydrogen, C1-C3 alkyl or fluorine.Preferred cyclic carbonate is ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, fluoroethylene carbonate (FEC) or its combination.In a preferred embodiment, the cyclic carbonate used in the electrolyte is propylene carbonate, fluoroethylene carbonate or its combination.
[0077] In one embodiment, the electrolyte may contain one or more solvents containing cyclic carbonates. If only one cyclic carbonate solvent is used, the solvent is preferably propylene carbonate. If two or more cyclic carbonate solvents are used, the solvent is preferably propylene carbonate and fluoroethylene carbonate.
[0078] Based on the total volume of the electrolyte, the solvent containing the cyclic carbonate can be present in the electrolyte in an amount of 5 to 75 volume % (vol%), preferably 10 to 50 and more preferably 20 to 40 volume %. For example, if a solvent containing a halogenated cyclic carbonate (e.g., fluoroethylene carbonate) is used in an electrolyte in combination with a solvent containing another cyclic carbonate, the solvent containing the halogenated cyclic carbonate is present in the electrolyte in an amount of 3 to 25 volume %, preferably 5 to 10 volume %, based on the total volume of the electrolyte.
[0079] The electrolyte preferably contains a linear carbonate solvent having a boiling point greater than 100° C. and a melting point preferably less than 0° C., preferably less than −25° C., and more preferably less than −50° C. The linear carbonate solvent used in the electrolyte has the structure of the following formula (2).
[0080] Wherein R3 and R4 can be identical or different, and be C1 to C6 alkyl or halogen independently.In one embodiment, R3 is C1 alkyl or C2 alkyl, and R4 is also C1 or C2 alkyl.In another embodiment, R3 is C1 alkyl or C2 alkyl, and R4 is C2 alkyl.The example of linear carbonate solvent comprises ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethyl butyrate (EB), methyl butyrate (MB) or its combination.
[0081] In another embodiment, the linear carbonate solvent may have the structure of formula (3)
[0082] wherein R5 and R6 are the same or different and are independently hydrogen or C1 to C5 alkyl. In a preferred embodiment, R5 is C1-C2 alkyl and R6 is hydrogen. Examples of solvents of formula (3) are methyl butyrate, ethyl butyrate, methyl 2-methyl butyrate or a combination thereof.
[0083] If only one linear carbonate solvent is used, the solvent is preferably one of ethyl methyl carbonate or diethyl carbonate. If two or more linear carbonate solvents are used, the solvent is preferably ethyl methyl carbonate and diethyl carbonate. In one embodiment, ethyl methyl carbonate and diethyl carbonate are added to the electrolyte in a volume ratio (ethyl methyl carbonate / diethyl carbonate) of 3 / 5 to 3 / 9, preferably 3 / 6 to 3 / 8.
[0084] The linear carbonate-containing solvent may be present in the electrolyte in an amount of 5 to 87 volume % (vol %), preferably 10 to 50 vol %, and more preferably 20 to 40 vol %, based on the total volume of the electrolyte.
[0085] In one embodiment, the total amount of the solvent containing cyclic and linear carbonates is present in the electrolyte in an amount of 10 to 50 volume %, preferably 20 to 40 volume %, based on the total volume of the electrolyte used in the pouch cell.
[0086] The electrolyte used in lithium-ion batteries contains a lithium salt in addition to a co-solvent. It is desirable that the lithium salt completely dissolves and dissociates in the electrolyte and that the solvated lithium ions (Li +) should have high mobility for ion transport. Anions should be stable to oxidative decomposition at the cathode and reductive decomposition at the anode. Examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalato)borate (LiBOB), lithium (difluoromethanesulfonyl) (trifluoromethanesulfonyl)imide (LiDFTFSI), lithium difluorooxalato borate (LIODFB), lithium difluorophosphate (LiPO2F2), lithium iodide (LiI), lithium bromide (LiBr), lithium chloride (LiCl), lithium thiocyanate (LiSCN), lithium nitrate (LiNO3), lithium nitrite (LiNO2), lithium sulfate (Li2SO4) or a combination thereof. A preferred lithium salt is lithium hexafluorophosphate (LiPF6). The lithium salt is added to the electrolyte in a molar amount of 0.6 to 2.0M, preferably 0.8 to 1.2M.
[0087] In one embodiment, the electrolyte may contain a primary lithium salt and a secondary lithium salt. The preferred primary lithium salt is lithium hexafluorophosphate (LiPF6), and the secondary lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalato)borate (LiBOB), lithium (difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide (LiDFTFSI), lithium difluorooxalatoborate (LIODFB), etc. or a combination thereof.
[0088] The lithium salt is present in the electrolyte in an amount of 7 to 20 weight percent (wt%), preferably 9 to 13 weight percent, based on the total weight of the electrolyte. The lithium salt may be diluted with water before being introduced into the lithium ion battery. For example, the lithium salt may be added to the pouch cell at a concentration of up to 2.0 M (molar), preferably 0.8 M to 1.2 M.
[0089] Additives may optionally be added to the electrolyte. The additive may include other solvents, phosphites and / or phosphates, sulfates, or combinations thereof to improve battery performance. Examples of additive solvents include vinylene carbonate, 1,3-propane sultone, or combinations thereof. The additive phosphite may include tris(trimethylsilyl)phosphite (TMSPi), and the additive phosphate may include tris(trimethylsilyl)phosphate (TTSP). Sulfates of 1,3,2-dioxathiolane 2,2-dioxide (DTD) and / or trimethylene sulfate (TMS) may also be added to the electrolyte. These additives may be used alone or in any combination. Each additive may optionally be added in an amount of 0.1 to 10 wt %, preferably 0.5 to 3 wt %, based on the total weight of the electrolyte.
[0090] The anode active layer 104 is disposed on the anode current collector 102. The cathode active layer 110 is disposed on the cathode current collector 112. The anode active layer generally comprises an anode active material disposed on the current collector and dried to form the anode active layer. The cathode active layer generally comprises a cathode active material disposed on the current collector and dried to form the cathode active layer. In addition to the anode active material, the anode active material generally comprises a conductive material and a polymer binder. In addition to the cathode active material, the cathode active material generally comprises a conductive material and a polymer binder. Sometimes a solvent can be used to produce a slurry, which is then disposed on the anode current collector or the cathode current collector and dried.
[0091] The anode active materials include some of the above carbonaceous materials, hard carbon, silicon, silicon mixed with graphite, silicon oxide mixed with graphite, carbon encapsulated silicon particles, Li4Ti5O 12 ; transition metals such as tin, metal oxides, metal sulfides, (e.g., TiO2, FeS, etc.) lithium metal and alloys or combinations thereof. Exemplary active materials may include graphite, hard carbon, activated carbon, nanoform carbon, silicon, silicon oxide, silicon oxide mixed with graphite, carbon-encapsulated silicon nanoparticles, or combinations thereof. In some such embodiments, the anode active material may be embedded with lithium (e.g., using pre-lithiation methods known in the art).
[0092] Hard carbon is a solid form of carbon that cannot be converted into graphite by heat treatment even at temperatures as high as 3000°C. It is also called char or non-graphitizable carbon. Hard carbon is produced by heating a carbonaceous precursor to about 1000°C in the absence of oxygen. Precursors of hard carbon include polyvinylidene chloride (PVDC), lignin, and sucrose. Other precursors, such as polyvinyl chloride (PVC) and petroleum coke, produce soft carbon or graphitized carbon. Soft carbon can be easily converted into graphite by heating to 3000°C.
[0093] In one embodiment, silicon and / or silicon oxide mixed with graphite can be used as the anode active material. Silicon monoxide and silicon suboxides (SiOx) are promising anode materials for lithium-ion batteries that provide high specific capacity and improved cycle performance, with some similarities to Si anodes. Although lithium oxide (Li2O) and lithium silicate (Li4SiO4) generated by the reaction of lithium ions with SiOx during the first lithiation process reduce the theoretical capacity, they also act as buffer components to accommodate the volume change caused by the further reaction of Si with Li in SiOx, thereby improving the cycle performance. In one embodiment, it is desirable to use a material having the formula Li y SiO x and Li y SiO x-C lithiated silicon oxide (LSO), wherein y is 0 to 1 and x is 0 to 2. The LSO may be in the form of nanotubes, nanofibers, nanosheets, nanoparticles or microparticles.
[0094] In a preferred embodiment, the anode active material comprises silicon oxide mixed with graphite. The silicon oxide can be lithiated before or after mixing with the graphite. The anode active material can be used in the anode active layer in an amount of greater than 20 wt %, preferably 30 to 60 wt %, based on the total weight of the anode active layer.
[0095] Conductive materials, polymer binders and solvents are used for both the anode active layer and the cathode active layer. All three components - conductive materials, polymer binders and solvents - are first described in detail below. Various conductive materials that can be used for the anode active layer or the cathode active layer are described in detail below.
[0096] The conductive additive preferably comprises a conductive carbonaceous material. Examples of conductive carbonaceous materials include carbon nanotubes, carbon black, activated carbon, graphene, graphite, graphite oxide, carbon fibers, etc., or a combination thereof. It is desirable that the conductive composition forms a conductive network extending from the surface of the current collector to the surface of the electrode (to contact the electrolyte).
[0097] Carbon nanotubes include single-walled carbon nanotubes (SWNT), double-walled carbon nanotubes (DWNT), multi-walled carbon nanotubes (MWNT) or combinations thereof, and have a diameter of 2 to 100 nanometers, preferably 10 to 50 nanometers. They have a length of 20 to 10,000 nanometers, preferably 200 to 5000 nanometers. An aspect ratio greater than 10, preferably greater than 50 and more preferably greater than 100 is desirable.
[0098] Carbon black with a high surface area is preferred for use in electrodes. Carbon black (subtypes are acetylene black, channel black, furnace black, lamp black, and thermal black) is a material produced by the complete combustion of coal and coal tar, vegetable matter, or petroleum products (including fuel oil, fluid catalytic cracking tar, and ethylene cracking under limited air supply). Carbon black is a form of quasi-crystalline carbon with a high surface area to volume ratio, but lower than that of activated carbon. Carbon black with a surface area of 50 to 1000 m2 can be used in the slurry used to form the electrode. 2 / gm of carbon black. Examples of carbon black that can be used in the electrode forming slurry are KELTJEN TM Black or Super P.
[0099] Graphene is an allotrope of carbon consisting of a single layer of atoms arranged in a hexagonal lattice nanostructure. The graphene added to the slurry can be in the form of individual graphene sheets or in the form of multiple loosely connected graphene sheets. Each atom in the graphene sheet is connected to its three nearest neighbors through sigma bonds and delocalized pi bonds, which contribute to the formation of a valence band that extends across the sheet. This is the same type of bonding seen in carbon nanotubes and polycyclic aromatic hydrocarbons, as well as fullerenes and glassy carbon. The valence band touches the conduction band, making graphene a semimetal with unusual electronic properties that are best described by the theory of massless relativistic particles.
[0100] In one embodiment, the graphene can be in the form of graphene nanoplatelets (GNPs). Exfoliated graphite nanoplatelets contain nanoparticles containing graphite. These nanoparticles consist of small graphene stacks with a thickness of 1 to 15 nanometers and a diameter ranging from submicron to 100 microns.
[0101] Graphite particles can also be used in conductive compositions. Graphite is a natural occurrence of pure carbon with a hexagonal crystal structure arranged in several parallel levels known as graphene layers. In simple terms, a graphite particle consists of multiple graphene sheets arranged parallel to each other. This anisotropic structure gives graphite special properties, such as electrical conductivity or specific strength along individual layers. It is extremely heat-resistant, with a sublimation point of over 3,800°C, high thermal conductivity and chemical inertness.
[0102] Graphite oxide (GO), sometimes referred to as graphene oxide, graphite oxide, or graphitic acid, is a compound of carbon, oxygen, and hydrogen in varying proportions, obtained by treating graphite with strong oxidants and acids to dissolve excess metals. The most oxidized bulk product is a yellow solid with a C:O ratio of 2.1:1 to 2.9:1, which retains the lamellar structure of graphite, but with larger and irregular spacing. The bulk material disperses spontaneously in alkaline solutions, or can be dispersed in polar solvents by ultrasonic treatment to produce monomolecular sheets, which are called graphene oxide by analogy with graphene (a single-layer form of graphite). Graphene oxide sheets exist in the form of strong paper-like materials, membranes, films, and composites, and can be used in electrode-forming slurries used to prepare electrodes.
[0103] Carbon fibers have a diameter of 5 to 10 micrometers and are composed primarily of carbon atoms. They may have a length greater than 1000 micrometers, preferably greater than 10,000 micrometers. They are produced by stretching pitch or polyacrylonitrile polymer fibers at high pressure and temperatures exceeding 1500°C, preferably at temperatures above 2200°C. Carbon fibers are different from carbon nanotubes and do not have concentrically arranged cylindrical graphene sheets. Carbon fibers typically contain high aspect ratio graphene sheets arranged in a parallel configuration to each other.
[0104] The above carbon nanotubes, carbon black, activated carbon, graphene sheets, graphite particles, graphite oxide particles or combinations thereof may be used alone or in any combination to form a conductive network. In an exemplary embodiment, carbon nanotubes are generally used in the largest amount when compared to other carbonaceous components.
[0105] The active layer may contain the conductive additive in an amount of up to 10% by weight, preferably 0.5 to 3% by weight, based on the total weight of the active layer.
[0106] The electrode forming slurry also optionally includes a polymer binder. The polymer binder binds the conductive additive and the active material so that they remain in contact with the current collector and are not dispersed in the electrolyte during the manufacturing process or use. The polymer binder preferably does not reduce the conductivity of the active layer disposed on the current collector. The active layer includes a conductive additive and a corresponding anode or cathode active material.
[0107] The polymer binder for each electrode (anode 120 or cathode 130) is preferably a fluorine-containing homopolymer or copolymer. In a preferred embodiment, the binder is a fluorine-containing copolymer. In one embodiment, the fluorine-containing copolymer is poly (vinylidene fluoride-co-chlorotrifluoroethylene) (abbreviated as P (VDF-CTFE)), poly (vinylidene fluoride-trifluoroethylene) copolymer (abbreviated as P (VDF-TeFE)), poly (vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer (abbreviated as P (VDF-TrFE-CFE)), poly (vinylidene fluoride-hexafluoropropylene) copolymer (abbreviated as P (VDF-HFP) or PVDF-HFP) or at least one of its combination. In a preferred embodiment, the polymer binder used in the active layer is a poly (vinylidene fluoride-hexafluoropropylene) copolymer. In another embodiment, the binder may include carboxymethyl cellulose (CMC) combined with styrene-butadiene rubber (SBR) or carboxymethyl cellulose combined with styrene-butadiene rubber and polyacrylic acid (PAA). The polymer binder has a weight average molecular weight of 5,000 to 1,000,000 g / mole, preferably 50,000 to 750,000 g / mole, and more preferably 75,000 to 500,000 g / mole as measured using gel permeation chromatography with polystyrene standards.
[0108] In one embodiment, the polyvinylidene content of any of the foregoing binders is 80 to 95% by weight based on the total weight of the polymer binder. The remaining polymer content of the copolymer is 5 to 20% by weight based on the total weight of the polymer binder. For example, if the polymer binder is a poly(vinylidene fluoride-hexafluoropropylene) copolymer, the polyvinylidene content of the copolymer is 80 to 95% by weight based on the total weight of the polymer binder, and the polyhexafluoropropylene content of the copolymer is 5 to 20% by weight based on the total weight of the copolymer.
[0109] After removing the solvent, the total weight of the polymer binder in the active layer is less than 10 weight %, preferably less than 8 weight %, and more preferably less than 6 weight %, and more preferably less than 5 weight % of the total weight of the active layer. If a polymer binder is present, it is present in an amount greater than 0.1 weight % of the total weight of the active layer. The lower weight of the polymer binder in the active layer is conducive to a lower reduction in the electrical conductivity of the active layer. In other words, the lower the amount of the polymer binder, the greater the electrical conductivity of the active layer. The active layer is arranged on a current collector and comprises a related (anode or cathode) active material, a conductive additive and a polymer binder.
[0110] Layered structure materials rich in lithium (Li) and manganese (LMR) can be used as cathode active materials. Lithium-rich manganese (LMR) layered oxides, also known as overlithiated oxides (OLO), have attracted attention as cathode materials for lithium-ion batteries due to their high capacity (greater than 250 mAh / g) and energy density. The following equation (1) provides an example of LMR:
[0111] (p)Li2MnO3(1-p)LiR1O2(1),
[0112] wherein R1 is Mn, Ni or Co and p is greater than 0 and less than 1.
[0113] The following equation (2) provides another example of LMR:
[0114] Li (2-x-y) R x M y O2(2),
[0115] Wherein R is Ni and M is at least one of Mn, Ni, Co or Al, wherein x+y<1 and wherein x is greater than 0.1 and less than 0.5.
[0116] An example of an LMR is Li[Li 1 / 3 Mn 2 / 3 ]O2 (commonly designated as Li2MnO3) and LiR1O2 (where R1 is nickel). Other LMRs that can be used in the cathode active layer include lithium manganese oxide (LMO with variants of LiMn2O4, Li2MnO3, etc.), LiNbO3-coated LiMn2O4, and Al-doped LiMn2O4.
[0117] Examples of other LMRs include lithium cobalt oxide (LCO, sometimes called "lithium cobaltate" or "spodumene" - one variant is LiCoO2); lithium nickel manganese cobalt oxide (NMC, a variant is LiNiMnCo); lithium nickel cobalt aluminum oxide (LiNiCoAlO2 and its variant NCA) and lithium titanate oxide (LTO, a variant is Li4Ti5O 12 ); lithium iron phosphate oxide (LFP, one variant of which is LiFePO4), lithium nickel cobalt aluminum oxide (and its variant NCA) and other similar materials, spinels (LiMn2O4, LiNi 0.5 Mn 1.5 O4), polyanion cathodes (LiV2(PO4)3), and other lithium transition metal oxides. Low voltage cathode materials (e.g., lithiated metal oxides / sulfides (e.g., LiTiS2), lithium sulfide, and sulfur) can also be used.
[0118] Other variations of the foregoing may be included. In some embodiments where NMC is used as the active material, a nickel-rich NMC may be used. For example, in some embodiments, a variation of NMC may be LiNi x Mn y Co (1-x-y) O2、LiNi x Mn y Al (1-x-y) O2、LiNi x Mn (1-x) O2、Li 1+x MO2 or a combination thereof, wherein x is equal to or greater than about 0.7, 0.75, 0.80, 0.85 or greater and wherein y is less than 0.15, preferably less than 0.1. In some embodiments, NMC811 may be used, wherein in the foregoing formula x is about 0.8 and y is about 0.1.
[0119] In yet another embodiment, the lithium- and manganese-rich layered structure material is Li z Ni x Mn y Co (1-x-y) O2、LiNi x Mn y Al (1-x-y) O2、LiNi x Mn (1-x) O2 or a combination thereof, wherein y is equal to or greater than about 0.5 and wherein x is less than 0.4 and wherein z is equal to or greater than 1.0 and less than 1.5.
[0120] The cathode active materials may be used in the cathode active layer in an amount of 70 to 99 wt %, preferably 92 to 96 wt %, respectively, based on the total weight of the cathode active layer.
[0121] Electrode forming slurry can be prepared in several different ways. In one embodiment, in a method of manufacturing the corresponding electrode (anode or cathode), the conductive composition, polymer binder, anode or cathode active material and cosolvent (such as those listed above) can be mixed in a single mixing device such as a stirrer for an appropriate amount of time to form a slurry. The mixing time can be 30 minutes to 5 hours. The slurry with the appropriate active material is then arranged on the corresponding current collector to form an anode or cathode. The slurry is arranged on the current collector and then dried to form an active layer.
[0122] Drying can be carried out at a temperature of 100 to 170° C. for a period of 30 minutes to 10 hours, preferably 1 to 5 hours. Mixing is carried out in a planetary mixer, but other mixers such as Waring mixers, Henschel mixers, single-screw and multi-screw extruders can also be used.
[0123] The electrolyte containing the co-solvent and the anode containing LSO can be used in a lithium ion battery pack used in the form of a pouch cell, a wound cell or a cylindrical cell. In a preferred embodiment, the lithium battery pack containing the above ingredients is in the form of a pouch cell.
[0124] Pouch cell 100 (see Figure 1 ) is a soft battery pack design in which most of the battery components are encapsulated in an aluminum-coated plastic film. Only two terminals 202 and 204 protrude from the bag. Each terminal is welded to one of the current collectors 102 and 112 in the bag 103. These high-conductivity electrode tabs are in electrical communication with the anode 120 and cathode 130 and allow power to be taken out of the pouch battery 100.
[0125] Inside the bag 103, the battery components are arranged in a multi-layer repeated stack. Each stack contains three solid sheet layers, two active material layers and a liquid electrolyte layer. The three solid sheet layers include an anode current collector, a cathode current collector and a separator. The two active material layers include an anode active material that contacts the anode current collector (to form an anode 120) and a cathode active material that contacts the cathode current collector (to form a cathode 130). The liquid electrolyte layer 106 includes a cosolvent (e.g., a combination of solvents containing cyclic and linear carbonates) and a lithium salt. When the battery pack is charged or discharged, ions move between the cathode and the anode through the liquid electrolyte.
[0126] Now refer to it again Figure 1, the pouch cell 100 is typically manufactured by a hot lamination method. In the hot lamination method, the ingredients used to make the electrode, such as a binder, a solvent, a corresponding active material (cathode active material or anode active material), and a conductive material are first mixed together to form a uniform paste. These ingredients are mixed under vacuum to prevent bubbles from being stirred into the paste and to prevent moisture from contaminating the anode active material and the electrolyte. When the paste is uniform, it is moved to a machine called a coater, where it is poured onto a highly conductive metal foil sheet (the "current collector" in the final assembly). The coater then scrapes off excess paste and dries the remaining paste.
[0127] After drying, the semi-formed electrodes are placed in a roller press and compressed under high pressure to obtain the correct porosity and thickness of the final electrode sheet. The higher the porosity, the better the electron flow, thus improving the performance of the battery. At this point, the sheet can be cut into the desired shape and size, leaving a conductive tip at the top to contact the tab.
[0128] After the electrode sheets are prepared, the pouch cells 100 are assembled in a controlled environment to prevent moisture from damaging the lithium-ion battery cell components. The first step of assembly involves welding a metal strip to the current collector. This strip will later be used to secure the terminals 202 and 204. Traditionally, welding is done using ultrasonic welding, but laser welding is becoming more popular.
[0129] Using a stacking machine, separator 108 is placed between the electrodes to form a stack inserted into the bag. The stack is then laminated in a roll mill at a temperature of 60 to 85°C. The sides of the bag 103 are joined together by a process known as heat sealing, leaving one side open. Liquid electrolyte 106 is then added to the battery using an electrolyte filling system.
[0130] The bag 103 is then sealed using a vacuum sealer, and the assembly of the pouch battery 100 is completed. The bag 103 will protect the components and hold them together.
[0131] Pouch cells and the compositions disclosed herein will now be described in the following non-limiting examples.
[0132] Example
[0133] Example 1
[0134] This example was conducted to demonstrate the use and properties of a battery in a thermal lamination process. The thermal lamination process was conducted as described above. The pouch cell contained an LSO anode in an amount greater than 40 wt % based on the total weight of the active layer. Additional details of the pouch cell are provided below.
[0135] The cathode active layer has an area capacity of 5 mAh / cm 2) of nickel cobalt manganese aluminum (NCMA). The mass ratio of the components used in the cathode active layer is as follows: nickel cobalt manganese aluminum NCMA / Super P carbon black (SP) / single-walled carbon nanotubes (SWCNT) / polyvinylidene fluoride (PVDF) = 95 / 2.9 / 0.1 / 2. The density of the cathode active layer is 3.3g / cm 3 .
[0136] The cathode used in the pouch cell is a double-sided cathode having two cathode active material layers disposed on opposite sides of a cathode current collector (one layer on each side of the cathode current layer). The cathode current collector comprises aluminum metal having a thickness of 15 microns, having two cathode active layers - each cathode active layer having a thickness of 75 microns, disposed on opposite sides of the aluminum metal (one on each side of the aluminum current collector). The total cathode thickness is about 165 microns.
[0137] The anode active layer contains 37.56 wt% lithiated silicon oxide (LSO) and has a capacity of 5.5 mAh / cm 2 The mass ratio of the components in the cathode active layer is as follows: LSO / graphite / SP / SWCNT / carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) / polyacrylic acid (PAA) = 37.56 / 56.34 / 0.5 / 0.1 / 1.5 / 2.0 / 2.0. The density of the anode active layer is 1.45 g / cm 3 .
[0138] The anode used in the pouch cell is a double-sided anode having two anode active material layers disposed on opposite sides of an anode current collector (one layer on each side of the anode current layer). The anode current collector comprises copper metal having a thickness of 6 microns, having two anode active layers - each anode active layer having a thickness of 53 microns, disposed on opposite sides of the copper metal (one on each side of the copper current collector). The total anode thickness is about 112 microns.
[0139] The electrolyte used in the pouch cell is a lithium salt (1M LiPF6), a solvent (propylene carbonate and ethyl methyl carbonate in a volume ratio of 3 to 7, 5 wt% fluoroethylene carbonate and 1 wt% vinylene carbonate) and additives (1 wt% TMSPi, 1 wt% LiBOB, 1 wt% DTD).
[0140] When making pouch cells, the anode, cathode and electrolyte are stacked, and the steps of calendering, stamping, stacking, welding, pre-sealing, drying, electrolyte filling, molding, degassing, final sealing and sorting are included to manufacture stacked double-layer pouch cells in a drying room with a dew point of -45°C (minus 45°C). The capacity of the pouch cell is 3.7 ampere-hours (Ah) and the voltage range is 2.5-4.2V. Hot lamination is performed at 70°C for 1 hour and then at 80°C for 0.67 hours. The use of a solvent containing cyclic carbonate shortens the manufacturing time of the pouch cell from 46.2 hours to 2.9 hours.
[0141] Since a co-solvent containing a cyclic carbonate-containing solvent in addition to a linear carbonate-containing solvent is used in the electrolyte, no solvent swelling occurs (during the manufacturing process). Therefore, the pouch cell exhibits tolerance to high temperatures used during manufacturing and high temperatures that may be encountered during use.
[0142] Embodiment 2:
[0143] This example was conducted to determine the capacity of a pouch cell. The pouch cell used was that described in detail in Example 1. Figure 2 is a graph depicting voltage (V) (300) versus capacity ((Ah) - ampere-hours) (400) at 25°C and a capacity rate of 1C. The pouch cell is charged / discharged over a voltage range of 2.7-4.2V (relative to Li+ / Li). The pouch cell is charged to 4.2V at a current rate of 1C (see charge curve 500), held until C / 20, and then discharged to 2.7V at a constant current rate of 1C (see discharge curve 600).
[0144] Some characteristics of pouch cells are detailed in Table 1 below.
[0145] Table 1.
[0146]
[0147] Embodiment 3:
[0148] This example was conducted to determine the charge rate.For the charge rate test, the pouch cells were charged to 4.2V at 3C at 25°C, C / 20 taper, with a 3C rate. Figure 3 is another graph showing the state of charge (SOC) in percent (700) versus the charging time in minutes (800) taken to reach a specific charge level. Figure 3 It can be seen that without applying external pressure, 85% SOC was achieved within 20 minutes. This example shows that the disclosed pouch cell exhibits excellent charging capability.
[0149] Embodiment 4:
[0150] This example was conducted to determine the DC fast charge (DCFC) cycling performance. Panel stress was not used in these DCFC tests. Two identical pouch cells 902 and 904 were charged / discharged over a voltage range of 2.0-4.2V (relative to Li+ / Li). Each pouch cell was charged to 4.2V at a current rate of 2C, held until C / 20, and then discharged to 2.5V at a constant current rate of 1C. Figure 4A and 4B is a graph depicting the performance of two pouch cells during DCFC testing. Figure 4A is a graph depicting the discharge capacity retention (in percent) (900) versus the number of cycles (1000), and Figure 4B Voltage (V) (1010) is plotted against capacity (Amp-hours) (1020). From these results, it can be seen that both cells using electrolytes containing cyclic carbonates exhibit good DCFC cycling performance.
[0151] It can be seen from the above embodiments that compared with conventional electrolytes based on linear carbonate solvents (such as ethyl carbonate and dimethyl carbonate), the electrolyte based on cyclic carbonates inhibits the expansion of pouch cells (having 30 to 40 wt % lithiated silicon oxide) during 80°C thermal lamination, and in addition to exhibiting enhanced DCFC cycle life and low-temperature discharge capability (-20°C to 25°C 1C capacity retention rate greater than 55%), it also exhibits excellent fast charging capability (reaching 85% SOC in 20 minutes).
[0152] The terms "a" and "an" do not indicate a quantitative limitation, but rather indicate the presence of at least one of the referenced items. The term "or" means "and / or" unless the context clearly indicates otherwise. References to "an aspect" throughout the specification mean that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in the various aspects.
[0153] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0154] Unless otherwise specified herein, all test standards are the most current standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which such test standard appears.
[0155] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0156] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be substituted with equivalents without departing from its scope. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the present disclosure without departing from its essential scope. Therefore, the present disclosure is not intended to be limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.
Claims
1. An electrolyte comprising: lithium salts; and A co-solvent; wherein the co-solvent comprises a solvent containing a cyclic carbonate and a solvent containing a linear carbonate.
2. The electrolyte of claim 1, wherein the lithium salt comprises a primary lithium salt and a secondary lithium salt; wherein the primary lithium salt is LiPF6; and wherein the secondary lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalato)borate (LiBOB), lithium (difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide (LiDFTFSI), lithium difluorooxalatoborate (LIODFB), or a combination thereof.
3. The electrolyte according to claim 1, wherein the lithium salt is LiPF6. 4 . The electrolyte according to claim 1 , wherein the cyclic carbonate-containing solvent comprises a 5-membered ring having a carbonate moiety, which has a boiling point greater than 200° C. and a melting point less than 50° C.
5. The electrolyte according to claim 1, wherein the cyclic carbonate-containing solvent has a structure of formula (1): wherein R1 and R2 may be the same or different and are independently hydrogen, C1 to C5 alkyl or halogen. 6 . The electrolyte according to claim 1 , wherein the cyclic carbonate-containing solvent is propylene carbonate (PC), fluoroethylene carbonate (FEC), or a combination thereof. 7 . The electrolyte according to claim 1 , wherein the linear carbonate-containing solvent is ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl butyrate, methyl butyrate, or a combination thereof.
8. A battery pack comprising: anode; wherein the anode comprises an anode current collector and an anode active layer; wherein the anode active layer comprises lithiated silicon oxide or a combination of lithiated silicon oxide and carbon; wherein the lithiated silicon oxide or a combination of lithiated silicon oxide and carbon is present in an amount of 20 wt % or greater based on the total weight of the anode active layer; Cathode; wherein the cathode comprises a cathode current collector and a cathode active layer; A separator disposed between the anode and the cathode; and An electrolyte; wherein the electrolyte comprises a lithium salt and a co-solvent; wherein the co-solvent comprises a solvent containing a cyclic carbonate and a solvent containing a linear carbonate.
9. The battery pack of claim 8, wherein the lithiated silicon oxide has the formula Li y SiO x And wherein the combination of lithiated silicon oxide and carbon has the formula Li y SiO x -C; wherein y is 0 to 1, and x is 0 to 2; wherein the cyclic carbonate-containing solvent comprises a 5-membered ring having a carbonate portion having a boiling point greater than 200°C and a melting point less than 50°C; and wherein the linear carbonate-containing solvent is ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl butyrate (EB), methyl butyrate (MB) or a combination thereof.
10. A method for manufacturing a lithium ion battery pack, comprising: stacking the anode, cathode and separator together; wherein the separator is disposed between the anode and the cathode; wherein the anode comprises an anode active layer comprising lithiated silicon oxide or a combination of lithiated silicon oxide and carbon in an amount of 20 wt % or greater based on the total weight of the anode active layer; contacting the anode and the cathode with an anode terminal and a cathode terminal, respectively; placing the anode and the cathode into a bag; laminating the bag in which the anode, the cathode, and the separator are disposed at a temperature of 60° C. to 85° C. to form a laminate; and An electrolyte is disposed in the bag to form a lithium ion battery; wherein the electrolyte comprises a lithium salt and a co-solvent; wherein the co-solvent comprises a cyclic carbonate-containing solvent and a linear carbonate-containing solvent.